(untitled) (Eurasian Scientific Herald, 2023)
This article deals with the investigation of the problems of phraseology in modern linguistics as well as cognitive approaches to these problems. One of the main problems is the translation of phraseological units considering lingo-cultural factors.Moreover, it is noticed translating of a regalia refers to meanings transforming it into phraseologies. In each cultural context there are typical modes of expression that assemble words in order to signify something that is not limited to the sum of the meanings of the single words.